Eﬀects of CdS quantum dots synthesized by various biological systems on cancer cells - Nikolaienko, T. V.; Nikulina, V. V.; Petruk, N. A.; Prysyazhnyuk, A. I.; Scachkova, O. V.; Borovaya, M. N.; Pirko, Ya. V.; Garmanchuk, L. V.; Tolstanova, G. M.; Yemets, A. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
Three types of semiconductor CdS nanoparticles (quantum dots) are obtained by biosynthesis, using bacteria Escherichia coli, the fungus Pleurotus ostreatus, and the plant — Linaria maroccana. The eﬀects of CdS quantum dots on the cancer cell line HeLa is studied. All types of CdS quantum dots vs ionic Cd2+ have weaker cytotoxic and cytostatic activities. The eﬀects on cells’ adhesive potential depend on the types of CdS quantum dots. The least toxic quantum dots are synthesized, using the fungus Pleurotus ostreatus. Low toxic eﬀects of studied ﬂuorescent CdS nanoparticles on cancer cells might promise their eﬀective application to cell biology and biomedical research.